Factors influencing job performance among police officers in Northern State of Malaysia - Noorliana, Mohamed Yunus (2019)
This study examines factors that influence job performance namely emotional intelligence, affective commitment and perceived organizational support. Data were collected from 219 rank and file police officers in Timur Laut, Penang. Instrument are taken from valid and reliable sources. Job performance instrument were adapted from Yu (1996), emotional intelligence instrument taken from Wong and Law (2002), affective commitment instrument based on Allen and Meyer (1990) and perceived organizational support instrument is from Eisenberger et. Al (1986). The result were analyzed with Statistical Package for Social Science (SPSS) version 25 and the findings indicated that emotional intelligence and affective commitment influence job performance but perceived organizational support did not influence job performance among the rank and file police officers. This study conclude by highlighting future research on ways to increase job performance among the police officers particularly in the context of Malaysia.